Pewarisan dan Keberlanjutan Identitas Hindu Bali Melalui Praktik Sosial dan Reproduksi Identitas dalam Relasi Minoritas-Mayoritas Agama di Daerah Transmigrasi - Agung Adi (Jayapangus Press, 2026)
The intergenerational transmission and continuity of Balinese Hindu identity within minority–majority religious relations in transmigration areas presents complex dynamics, especially when structural pressures, differences in the number of adherents, and cultural dominance influence the space for religious practice. This study aims to analyze social practices, identity reproduction mechanisms, and negotiation processes carried out by Balinese Hindus in the transmigration area of Sumber Garunggung Village, Central Kalimantan, while also formulating the implications for the sustainability of identity as a minority group. A qualitative approach was used with participatory observation, in-depth interviews, and documentation techniques. Data analysis is based on Pierre Bourdieu's theory of practice, particularly related to the concepts of habitus, arena, and capital, and is supported by Stuart Hall's theory of cultural identity regarding identity as a dynamic or fluid process. The results of the study show that Balinese Hindu identity is reproduced through rituals, religious and customary institutions, family, pasraman, art, and socio-economic activities. Identity negotiation takes place dialogically and contextually, particularly through adjustments to the ngaben ritual, interfaith participation, rational symbolic communication in public spaces, and the strengthening of social and economic capital to gain legitimacy. These findings confirm that identity is not merely inherited but is reproduced through continuous interaction between structure and agency. This study formulates the “Contextual-Transmigratory Balinese Hindu” model, which is a pattern of identity that is stable in the core values of Balinese Hindu teachings, yet adaptive in practice according to the social context. The sustainability of minority identity depends on normative stability, social legitimacy, and contextual adaptability.